2016
DOI: 10.3389/fnhum.2016.00640
|View full text |Cite
|
Sign up to set email alerts
|

Refining an Asynchronous Telerehabilitation Platform for Speech-Language Pathology: Engaging End-Users in the Process

Abstract: Asynchronous telerehabilitation in which computer-based interventions are remotely monitored and adapted offline is an emerging service delivery model in the rehabilitation of communication disorders. The asynchronous nature of this model may hold a benefit over its synchronous counterpart by eliminating scheduling issues and thus improving efficiency in a healthcare landscape of constrained resource allocation. The design of asynchronous telerehabilitation platforms should therefore ensure efficiency and flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 37 publications
1
59
0
1
Order By: Relevance
“…It is acknowledged that participatory design approaches rely heavily on effective communication between the participants and designers and thus may be challenging for people with poststroke aphasia [78]. However, there are numerous examples of people with poststroke aphasia successfully partaking in participatory design studies to enhance the usability of aphasia-specific programs [19,78-82].…”
Section: Discussionmentioning
confidence: 99%
“…It is acknowledged that participatory design approaches rely heavily on effective communication between the participants and designers and thus may be challenging for people with poststroke aphasia [78]. However, there are numerous examples of people with poststroke aphasia successfully partaking in participatory design studies to enhance the usability of aphasia-specific programs [19,78-82].…”
Section: Discussionmentioning
confidence: 99%
“…Computerized homebased therapy for aphasia has been delivered through software programs (e.g., AphasiaScripts TM ) (13), specifically designed apps (e.g., TACTUS Language therapy © ) (14), and generic apps (e.g., iBooks) (9). Asynchronous tele-rehabilitation is a service delivery model that enables patients to carry out independent practice of computer-based rehabilitation interventions in their own time, with monitoring and adaption of therapy exercises carried out asynchronously (15). The Big CACTUS trial was the first fully powered, randomized controlled trial to evaluate the clinical and cost-effectiveness of computer speech and language therapy for aphasia in the long-term post stroke (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond circumventing these constraints, such therapies can be leveraged to increase the intensity of treatment as they are accessible from any setting at any time (1,(6)(7)(8)(9)(10)(11)(12). Furthermore, even when therapy is administered remotely, clinicians are able to monitor progress and tailor therapy to a client's unique needs (4,5,8,(13)(14)(15). Recent work by Kiran et al (16) demonstrated that utilizing tablet-based language rehabilitation can simultaneously increase the intensity of practice while also tailoring treatment to the individual participant's needs.…”
Section: Introductionmentioning
confidence: 99%